2012
DOI: 10.1155/2012/872176
|View full text |Cite
|
Sign up to set email alerts
|

Association ofFTOPolymorphisms with Early Age of Obesity in Obese Italian Subjects

Abstract: Obesity is recognized as a major health problem worldwide. Genetic factors play a major role in obesity, and genomewide association studies have provided evidence that several common variants within the fat mass- and obesity-associated (FTO) gene are significantly associated with obesity. Very limited data is available on FTO in the Italian population. Aims of our study are to investigate: (1) the association of FTO gene SNPs rs9939609 and rs9930506 with body mass index (BMI) and obesity-related parameters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
49
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 25 publications
20
49
0
6
Order By: Relevance
“…Our findings are in concordance with previous studies reporting the association of the FTO A allele with increased BMI and that the frequency of the A allele in our study was similar to that observed in other populations ranging from 45 to 48% [4, 20]. This may suggest that the effects of environmental factors on obesity in Kuwait are larger than genetic factors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in concordance with previous studies reporting the association of the FTO A allele with increased BMI and that the frequency of the A allele in our study was similar to that observed in other populations ranging from 45 to 48% [4, 20]. This may suggest that the effects of environmental factors on obesity in Kuwait are larger than genetic factors.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with recent findings showing that different variants within the FTO gene are associated with different classes of obesity [6]. Moreover, a study by Sentinelli et al [20] showed an association between the common FTO rs9939609 polymorphism with BMI in an Italian population; however, a stronger association was observed with another polymorphism, rs9930506, within the FTO gene suggesting the impact of other polymorphisms on BMI. This also supports findings that the impact of FTO on obesity is population-dependent [20, 22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some meta-analysis studies have found a relationship among FTO and specific cancer types, including PCa [16,2123]. All these findings are related to a cluster of single-nucleotide SNPs (SNPs) in the FTO gene first intron which is inherited in linkage disequilibrium (LD) [9,15,18,24,25], and includes among others the rs9930506 and rs9939609 SNPs as reported by Loos et al [26]. In this GWAS study done by Loos’ group with an admixed American population which included participants from Colombia, Mexico and PR, they found that the above mentioned FTO SNPs among others, are related in a statistically significant manner to an increased BMI [26].…”
Section: Introductionmentioning
confidence: 99%
“…In FTO rs9930506 , the single nucleotide transition of an adenine nucleotide to a guanine nucleotide has been reported to be significantly associated to BMI, particularly when the rare “G” allele is present in the homozygous form [25,27]. In addition, in FTO rs9939609 , the single nucleotide transversion of a thymine nucleotide to an adenine nucleotide has been associated with both BMI and type-2 diabetes, in either the heterozygous or the homozygous forms of the mutated “ A ” allele [25,28].…”
Section: Introductionmentioning
confidence: 99%